Analisis makna kontekstual hadis peranan ibu terhadap pembentukan spiritual anak berdasarkan Hadis Sahih al-Bukhari (contextual analysis of the Hadith from Sahih al-Bukhari regarding the role of mothers in shaping the children’s spiritual development) - Mohd Ghazali, Norzulaili; Abd Manan, Mawaddah; Mohamed Nor, Zulhilmi; Mohd, Robiatul Adawiyah; Ahmad, Nadzrah (USIM Press, 2023)
The disregard for the spiritual dimension of children, particularly within the contemporary technological era, contributes significantly to the erosion of ethical values within familial domains. Therefore, the spiritual formation of children must be emphasized by parents, with a particular emphasis on mothers, who occupy the most proximate role in their children's lives. The exemplary source of spiritual formation is the teachings of Prophet Muhammad (PBUH), as he is the best example to follow in family life. Thus, this study aims to extract hadiths from Sahih al-Bukhari regarding the role of mothers in shaping the spiritual development of children. The extracted hadiths will be analyzed to identify the contextual meanings of these hadiths. This study employed the qualitative method based on the text analysis approach using the extraction of hadiths related to the role of mothers from Sahih al-Bukhari, applying the Theory of Semantic Fields (SFT) for the term "umm" (mother). This theory is applied to identify hadiths related to the role of mothers based on the term "umm" and its synonyms, antonyms, hypernyms, and meronyms. The result of the study shows a total of 5 hadiths directly related to the spiritual formation of children. These 5 hadiths encompass aspects of instilling faith, adopting an approach to train children in performing worship, and praying for children. In conclusion, spiritual formation within children, guided by the hadiths of the Prophet Muhammad, peace be upon him, serves as a comprehensive guide to shaping their character and nurturing them into pious individuals.